Balas de carmín - García Francés, Alfredo, 1949- (Editorial Oveja Negra : Quintero Editores, 2007)
When Lany, the daughter of a prosperous Colombian family, is kidnapped and remains in captivity, she becomes a member of a violent drug gang and a lover of women who cannot escape the consequences of her past no matter where she goes.